Вклад системы образования в решение проблемы социального неравенства - Цымбал, Светлана Николаевна (International Dialogues on Education Journal, 2016)
The article analyzes the role of quality education in solving the problems of social inequality, polarization and marginalization of society. It characterizes the negative effects of exclusion of vulnerable groups of the population from public life. The article investigates the vulnerable groups in Ukraine: people with disabilities, residents of remote settlements, families with many children, separate groups of migrants, the poor. It discusses the causes of unequal access to quality education at the macro level and the micro level. At the macro level the educational system is analyzed as a whole, at the micro level the possibility of an individual is illuminated. The article deals with the impact of economic barriers to providing equal educational opportunities for all population groups in the education system. Special attention is paid to the system of events aimed at improving the quality of educational services, mitigation of social inequality, increased access of vulnerable populations to educational resources. The article substantiates the potential opportunities of free public access to all levels of quality education to improve the competitiveness of people in the labor market, and to improve the prospects of their socio-economic development.